Sex differences in HPV immunity among adults without cancer. Issue 7 (3rd August 2019) - Windon, Melina J.; Waterboer, Tim; Hillel, Alexander T.; Chien, Wade; Best, Simon; Stewart, Charles; Akst, Lee; Troy, Tanya; Bender, Noemi; Miles, Brett; Ryan, William R.; Mandal, Rajarsi; et al.
ABSTRACT: The incidence of human papillomavirus (HPV)-associated head and neck cancers is rising, particularly among men. Whether observed epidemiological differences in sex are explained by differences in sexual exposure and/or by immune response is unclear. In this cross-sectional, multi-institutional study, seroprevalence of antibodies to HPV L1 capsid antigen was compared by patient characteristics among 374 adult patients without cancer. A significantly higher seroprevalence was observed among women compared with men for HPV16 (OR = 2.96, 95% CI = 1.21–7.21) and HPV18 (OR = 2.84, 95% CI = 1.06–7.60) L1 antibodies. This difference persisted for HPV16 after controlling for lifetime and recent sexual behavior. After controlling for sex, HPV16 and HPV18 L1 seroprevalence was also significantly associated with higher number of lifetime (HPV16 OR = 1.05, 95% CI = 1.01–1.08; HPV18 OR = 1.04, 95% CI = 1.01–1.08) and recent (HPV16 OR = 1.54, 95% CI = 1.15–2.07; HPV18 OR = 1.40, 95% CI = 1.07–1.82) oral but not vaginal sexual partners. These findings potentially suggest a more robust immune response to HPV16/18 among women compared with men that may not be explained by differences in number of sexual partners, and thereby presumably HPV exposure. The independent association of HPV16/18 L1 seroprevalence with higher number of oral sexual partners suggests a possible role for site of mucosal exposure in the HPV immune response.